Grade influences blood lactate kinetics during cross-country skiing - LaRoche, D. P.; Amann, M.; Rundell, K. W. (The Journal of Strength and Conditioning Research, 2010)
The purpose of this study was to examine the effects of level vs. graded skate skiing on capillary blood lactate (B(La)), heart rate (HR), oxygen consumption (V(O2)), and training intensity prescriptions. Eleven Nordic skiers completed 2 submaximal skate roller skiing treadmill protocols during which intensity was increased either by grade (G(inc)) or by speed (S(inc)). The protocols were compared for prethreshold BLa, HR, and V(O2) at lactate threshold (LT) and the HR/V(O2) relationship. Additionally, double-pole (primarily upper body) and skating (arms and legs combined) protocols were used to measure peak V(O2) and peak HR. Heart rate and V(O2) at LT were lower during G(inc) compared with S(inc) (154.9 +/- 6.8 b.min(-1) vs. 162.0 +/- 9.1 b.min(-1) and 46.3 +/- 2.8 ml.kg(-1).min(-1) vs. 49.1 +/- 1.6 ml.kg(-1).min(-1), respectively, both p < 0.01). Pre-threshold B(La) and the HR/V(O2) relationship were not different between the submaximal protocols. V(O2) and HRpeak were higher in skating compared with double poling (64.6 +/- 1.8 ml.kg(-1).min(-1) vs. 60.3 +/- 2.8 ml.kg(-1).min(-1), 192.6 +/- 5.8 b.min(-1) vs. 187.8 +/- 6.7 b.min(-1), respectively, both p < 0.01). Greater reliance on upper-body musculature during graded skiing and its associated lower aerobic capacity increases B(La) when compared with level skiing. The leftward shift in the B(La) vs. intensity curve during uphill skiing should be recognized to properly prescribe training intensity as well as interpret laboratory results.